Environmental effects of global value chain embedding in manufacturing industry in countries along the Belt and Road - Hairong Huang; Zhengyu Zhang; Fuxin Jiang (Frontiers in Environmental Science, 2022)
While embedding in the global value chain (GVC), avoiding becoming a “pollution shelter” is an urgent issue that needs to be solved for the low-carbon economic development of countries along the Belt and Road. This study empirically analyzes the impact of manufacturing GVC embedding on carbon emissions and its mechanism from the perspectives of the embedding position and degree of the GVC. It then carries out group regressions by different industries, value chain embedding modes, and so on. Finally, this study constructs static and dynamic panel models to verify the nonlinear relationship between manufacturing GVC embedding and carbon emissions. The results show that the improvement of the embedding position of GVC in the manufacturing industry promotes an increase in carbon emissions; the deeper the embedding degree of GVC, the more conducive it is to carbon emissions reduction. Compared with the service industry, the impact of manufacturing GVC embedding on carbon emissions is more significant; regardless of the value chain embedding model, the deeper the embedding degree, the more conducive it is to carbon emissions reduction. Technological progress can weaken the impact of GVC embedding on carbon emissions. There is a U-shaped relationship between the GVC embedding position and carbon emissions in the manufacturing industry and an inverted U-shaped relationship between the GVC embedding degree and carbon emissions. This study provides beneficial insights for countries along the Belt and Road to embed into the GVC to avoid falling into the dilemma of “pollution growth”.